Music divided : Bartók's legacy in cold war culture - Fosler-Lussier, Danielle, 1969- (California studies in 20th-century music, 2007)
In this groundbreaking study, the author illuminates the pervasive political anxieties of the era through particular attention to artistic, music-theoretical, and propagandistic responses to the music of Hungary's most renowned 20th century composer, Béla Bartók.